Penurunan Intensitas Nyeri Pada Pasien Pasca Operasi Melalui Teknik Relaksasi Genggam Jari Literatur Review - Rante, Anshar; Ananda Kasih, Putri Viola; Rasyid, Djusmadi (Barongko: Jurnal Ilmu Kesehatan, 2023)
The Finger Grip Relaxation Technique is an easy and simple technique that anyone can do. Its application is related to the fingers and the flow of energy in the body. This relaxation can then heat the entry and exit points of energy in the meridians (body or energy pathways) in the fingers, thereby causing reflex stimulation (spontaneous) when gripping. The finger tapping relaxation technique helps the soul, mind, and body relax. When conditions are relaxed, it triggers the natural release of endorphins, this is the hormone that naturally acts to relieve pain. Writing this proposed scientific article aims to determine the effectiveness of finger grip relaxation techniques in reducing pain intensity in postoperative patients. This study used a descriptive method with a literature review approach. The data source is secondary. Articles and some magazines serve as sources of information. The literature search strategy uses the PICO framework. The inclusion criteria are national and international research journals that discuss reducing pain intensity in postoperative patients using finger grip relaxation techniques, as well as articles or journals published after 2018 in English and Indonesian. An approach consisting of presentation methods and analytical methods is used for data analysis. The results obtained in this study regarding the effect of hand-held relaxation techniques on reducing pain intensity. Of the five research publications reviewed, all of them are effective in reducing pain using finger grip relaxation techniques. The interventions used were the results of five studies where there was a decrease in pain. This proves that finger-held relaxation techniques can reduce pain intensity in postoperative patients.